Alimentação de lactentes nascidos pré-termo no seguimento pós-natal - Bottoli, Claudiane (2024)
Objective: To verify the risk of dysphagia and pediatric eating disorders and the food consumption profile in infants born preterm, monitored in the premature infant follow-up clinic of a teaching hospital. Method: Observational, cross-sectional, analytical study with a quantitative approach. The sample comprised 64 premature infants fol-lowed at the follow-up clinic, who constituted the study group (GE) and 25 full-term infants, followed at the general pediatrics clinic, who constituted the control group (CG), all aged between 12 and 24. months. The data were collected on the day the infants had a medical appointment at the hospital, and the interview with the parents or guard-ians focused on their profile.sociodemographic, breastfeeding and food introduction. Screening protocols for dysphagia and pediatric eating disorders and food consump-tion markers were applied. Results: There was a predominance of artificial breast-feeding and supplemented breastfeeding in the EG and exclusive breastfeeding in the CG. The average duration of continued breastfeeding in the sample was 3.26 ± 4.79 months of corrected age in the EG and 6.0 ± 1.24 months in the CG. The EG presented a significantly higher risk for dysphagia than the CG. The risk for pediatric eating dis-orders was not different between groups. Regarding food consumption, a large part of the sample was not continuously breastfeeding. At the time of the assessment, both groups consumed fruits, solid salt foods, vegetables, meat, beans, rice, and had a low consumption of hamburgers and sweetened drinks. However, the CG had a high per-centage of sweets and stuffed biscuit intake. Conclusion: Exclusive breastfeeding rates were higher in the CG both at hospital discharge and at the time of introduction of complementary feeding. Complementary feeding started at an appropriate age for both groups and there was no association between the risk of pediatric eating disorders and premature birth. The risk of dysphagia was associated with prematurity.